Coordinate Regulation of Antimycin and Candicidin Biosynthesis - Thomas C. McLean (American Society for Microbiology, 2016)
ABSTRACT Streptomyces species produce an incredible array of high-value specialty chemicals and medicinal therapeutics. A single species typically harbors ~30 biosynthetic pathways, but only a few them are expressed in the laboratory; thus, poor understanding of how natural-product biosynthesis is regulated is a major bottleneck in drug discovery. Antimycins are a large family of anticancer compounds widely produced by Streptomyces species, and their regulation is atypical compared to that of most other natural products. Here we demonstrate that antimycin production by Streptomyces albus S4 is regulated by FscRI, a PAS-LuxR family cluster-situated regulator of the polyene antifungal agent candicidin. We report that heterologous production of antimycins by Streptomyces coelicolor is dependent on FscRI and show that FscRI activates the transcription of key biosynthetic genes. We also demonstrate through chromatin immunoprecipitation sequencing that FscRI regulation is direct, and we provide evidence that this regulation strategy is conserved and unique to short-form antimycin gene clusters. Our study provides direct in vivo evidence of the cross-regulation of disparate biosynthetic gene clusters specifying unrelated natural products and expands the paradigmatic understanding of the regulation of secondary metabolism. IMPORTANCE Natural products produced by members of the phylum Actinobacteria underpin many industrially and medically important compounds; however, the majority of the ~30 biosynthetic pathways harbored by an average species are not expressed in the laboratory. Understanding the diversity of regulatory strategies controlling the expression of these pathways is therefore critical if their biosynthetic potential is to be explored for new drug leads. Our findings reveal that the candicidin cluster-situated regulator FscRI coordinately controls the biosynthesis of both candicidin and antimycin, which is the first observation of cross-regulation of disparate biosynthetic gene clusters specifying unrelated natural products. We anticipate that this will emerge as a major strategy by which members of the phylum Actinobacteria coordinately produce natural products, which will advance our understanding of how the expression of secondary metabolism is controlled and will aid the pursuit of “silent” biosynthetic pathway activation.